(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Analytical essays represent a ubiquitous academic task, necessitating students to engage in a critical examination of a subject, issue, or textual material, and present substantiated arguments and analyses. This article delves into the categorization of analytical essays and their fundamental characteristics, to furnish a thorough comprehension of this genre of scholarly writing.